21-6(7y-4)=-40x+45

Simple and best practice solution for 21-6(7y-4)=-40x+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21-6(7y-4)=-40x+45 equation:


Simplifying
21 + -6(7y + -4) = -40x + 45

Reorder the terms:
21 + -6(-4 + 7y) = -40x + 45
21 + (-4 * -6 + 7y * -6) = -40x + 45
21 + (24 + -42y) = -40x + 45

Combine like terms: 21 + 24 = 45
45 + -42y = -40x + 45

Reorder the terms:
45 + -42y = 45 + -40x

Add '-45' to each side of the equation.
45 + -45 + -42y = 45 + -45 + -40x

Combine like terms: 45 + -45 = 0
0 + -42y = 45 + -45 + -40x
-42y = 45 + -45 + -40x

Combine like terms: 45 + -45 = 0
-42y = 0 + -40x
-42y = -40x

Solving
-42y = -40x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-42'.
y = 0.9523809524x

Simplifying
y = 0.9523809524x

See similar equations:

| 3/4x-1/2=x-7/4 | | (2t)(81t^1/2) | | 9+7d-5-8d= | | 20-26x=6x^2 | | f(5)=-4x+12 | | 3/4x-1/2=x-7/7 | | 4x=380 | | 1/3×x=6700 | | 2+6f=8 | | 89-2x=67 | | 7x-2x+10x+45=75 | | x-(8)=3x | | 3(b+2)+9=3b+15 | | (3x+8)+(4x+2)= | | 53x=795 | | 1/bxb | | 3(m-5)+5= | | (3b+5)+2b= | | 3x+2y+2z=360 | | 5x+7(8-x)=50 | | -(3-y)-(3+y)=2y-6 | | 2+5x=2y+10 | | n^2-3=14n | | 52-2x=8 | | -22=-5x+9 | | b^2-16b-57=0 | | 6x-14=-38 | | 2(6x-7)+4=10x-6+4x | | 9+3k+5k= | | 5x+13+7x-37=180 | | z2=25/36 | | 2(f-7)=6 |

Equations solver categories